Classifications of translation surfaces in isotropic geometry with constant curvature - Aydin , M. E. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 515.12We classify translation surfaces in isotropic geometry with arbitrary constant isotropic Gaussian and mean curvatures under the condition that at least one of translating curves lies in a plane.